Pathogenesis of central nervous system germ cell tumors - Liu, Siyuan; Ren, Linan; Gao, Xue; Hao, Mengjin; Wang, Guixia (Frontiers in Oncology, 2022)
Intracranial germ cell tumors (IGCTs) are clinically rare intracranial tumors that often occur in children and adolescents, with a higher incidence in Asia than in Western countries. Histologically, IGCTs are usually divided into two categories: Germinoma and non-germinomatous germ cell tumor (NGGCT). Most germinoma are sensitive to radiotherapy and chemotherapy, which have a good prognosis. However, NGGCT, especially NGGCT with malignant components, has poor sensitivity to radiotherapy and chemoradiotherapy，which have poor prognosis. The pathogenesis of intracranial germ cell tumors is not fully understood. By summarizing previous relevant literature, this review proposes that the occurrence of intracranial germ cell tumors may be related to the following factors: chromosomal instability, changes in MAPK and/or PI3K pathways, pure germ cells Tumor hypomethylation, etc.